2022
DOI: 10.1111/inr.12753
|View full text |Cite
|
Sign up to set email alerts
|

Testing a model of Thai nurses’ intent to stay in employment

Abstract: To test the causal model of intent to stay in employment of nurses in regional medical centers. Background: Effectiveness and quality of nursing care are determined by an adequate number of nursing staff; however, there is an ongoing challenge of nursing shortage. Improving nurses' intention to remain in employment is an effective way to address the problem of nursing shortage. Methods: This study employed a cross-sectional design. The sample was 1224 registered nurses from nine regional medical centers across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…The ITS of nursing faculty members increased when they were fulfilled in their positions and had strong bonds with the organization (Hodgkins et al, 2020). Similarly, the more satisfied they were with their job choices and their positions, the more likely they were to stay employed (Theucksuban et al, 2022). Scholars have mentioned that improving JS among nursing faculty members would improve ITS (Darnell et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The ITS of nursing faculty members increased when they were fulfilled in their positions and had strong bonds with the organization (Hodgkins et al, 2020). Similarly, the more satisfied they were with their job choices and their positions, the more likely they were to stay employed (Theucksuban et al, 2022). Scholars have mentioned that improving JS among nursing faculty members would improve ITS (Darnell et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Much is known about the regressive lag indicators and corrosive factors that cause intention to leave, which in up to 80% of cases can result in actual leavers (Applebaum et al, 2010; Kagwe et al, 2019; Perry et al, 2018), and yet there is limited insight into the forward‐looking indicators of why nurses stay and the potential of the positive impact on turnover. For that reason, while ever these factors remain undefined nurse retention is not being approached from a solution‐focused perspective (Kelly et al, 2022; Theucksuban et al, 2022); a seemingly missed opportunity in the face of the reality of the brittle global nurse workforce position.…”
Section: Introductionmentioning
confidence: 99%
“…It is seemingly evermore improbable that globally, we will be able to recruit into fixing the nursing workforce problem, and it is suggested that one part of the solution lies in retaining nurses already working within our healthcare systems. It is propositioned that significant gains to the nursing workforce are in the main, achievable through the implementation of effective strategies to retain existing staff and that nurse retention is the critical factor in counterbalancing the demand–supply equation (Sherman, 2014 ; Theucksuban et al, 2022 ; Van den Heede et al, 2013 ). Thus, there is an urgency to understand how to improve nurse retention to realise a turning point and support more nurses to stay (World Health Organization (WHO), 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Higher nurse turnover rates increase the workload, reduce job satisfaction and lead to physical and mental health problems for remaining workforce (Chang & Cho, 2022). Furthermore, increased nurse turnover rates result in a shortage of experienced nurses, making it difficult to provide high‐quality care to patients and increasing the risk of infection, hospitalization and death (Labrague et al., 2020; Theucksuban et al., 2022). Thus, the healthcare sector should focus on the problem of nurses’ turnover intention and develop practical prevention measures to encourage nurses to stay.…”
Section: Introductionmentioning
confidence: 99%